Beyond America's War on Drugs: Developing Public Policy to Navigate the Prevailing Pharmacological Revolution - Andrew Golub; Alex S. Bennett; Luther Elliott (AIMS Press, 2015)
This paper places America's "war on drugs" in perspective in order to develop a new metaphor for control of drug misuse. A brief and focused history of America's experience with substance use and substance use policy over the past several hundred years provides background and a framework to compare the current Pharmacological Revolution with America's Nineteenth Century Industrial Revolution. The paper concludes with cautions about growing challenges and provides suggestions for navigating this revolution and reducing its negative impact on individuals and society.